Smart solar aquarium / Muhd Aminur Rashid Zailan & Muhammad Hairul Fikry Jalal - Jalal, Muhammad Hairul Fikry; Zailan, Muhd Aminur Rashid (2015)
The solar energy is used as a power source to give supply in the project. The solar power will be stored in the battery bank and at the same time it charges the battery. The project is build to save the uses of power supply from the power station. In addition, this project is free pollution project. After the solar energy converted, it will be stored into a battery bank. In addition, this project is design to reduce the cost of electricity bill and at the same time it can operate during blackout. Then, the power will be supply to LED and buzzer. The LED will only function at night because it uses the light sensor. The buzzer will alert the owner to feed the fish every 12 hours. The timer is programmed in PIC16F877A microcontroller. It can be conclude that the uses of solar energy is more reliable and help saving budget thus it will help in conserving the environment. In other hand, by using microcontroller the whole process can be controlled.